SOURCES OF WORK SATISFACTION ON NON-CIVIL SERVANT TEACHERS IN RURAL VILLAGE OF KAMPUNG LAUT CILACAP - Qorry Akbar Firmansyah; Tri Na'imah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
The purpose and focus of this research are to find out the sources of work satisfaction on non-civil servant Primary School teachers in rural area of Kampung Laut. This qualitative research used phenomenology approach with 4 primary informants. The data were collected using interview. The credibility used by the researcher was inter-researcher triangulation. The results showed similarity and difference from the 4 informants. All of the informants stated that work satisfaction had several affecting factors. One of the satisfactions was when teacher had taught well and correctly to improve the students' knowledge so they could reach achievement index that the school wanted and helped their school to be better than before. Colleagues that helped and motivated each other resulted a passion at work and made the teachers satisfied with their work. The relationship between the leader and colleagues such as motivating each other, helping each other, and showing solidarity created a good working condition.